2022
DOI: 10.20885/jif.specialissue2022.art19
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity, total flavonoid, and total tannin content of ethanol extract of avocado peel (Persea americana Mill.)

Abstract: Background: Avocado is a plant that can grow in tropical climates. In general, people only consume the fruit while the skin and seeds are not used. Avocado fruit, skin and seeds contain secondary metabolites such as flavonoids and tannins which have antioxidant activity. Objective: To determine antioxidant activity, total flavonoid, and total tannin content of the ethanol extract of avocado peel. Methods: P. americana Mill. was collected from Lubuk Linggau, South Sumatra. The ethanol extract of P. american… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…in this study showed the presence of flavonoids and tannins. Flavonoids and tannins are a class of phenolic compounds with hydroxyl groups that can reduce free radicals [41]. Flavonoid compounds give color to plants and can be used as antioxidants also antibacterials [42].…”
Section: Bioactive Compounds Of Gracilaria Spmentioning
confidence: 99%
“…in this study showed the presence of flavonoids and tannins. Flavonoids and tannins are a class of phenolic compounds with hydroxyl groups that can reduce free radicals [41]. Flavonoid compounds give color to plants and can be used as antioxidants also antibacterials [42].…”
Section: Bioactive Compounds Of Gracilaria Spmentioning
confidence: 99%